Exploring Risk and Protective Factors in Parkinson’s Disease - Iman Beheshti (Cells)
Understanding the risk and protective factors associated with Parkinson’s disease (PD) is crucial for improving outcomes for patients, individuals at risk, healthcare providers, and healthcare systems. Studying these factors not only enhances our knowledge of the disease but also aids in developing effective prevention, management, and treatment strategies. This paper reviews the key risk and protective factors associated with PD, with a particular focus on the biological mechanisms underlying these factors. Risk factors include genetic mutations, racial predispositions, and environmental exposures, all of which contribute to an increased likelihood of developing PD or accelerating its progression. Conversely, protective factors, such as regular physical exercise, adherence to a Mediterranean diet, and higher urate levels, have the potential to reduce inflammation and support mitochondrial function, thereby mitigating the risk of disease. However, identifying and validating these factors presents significant challenges. These challenges include the absence of reliable biomarkers, intricate interactions between genetic and environmental components, and clinical heterogeneity observed in patients with PD. These barriers complicate the establishment of clear causal relationships and hinder the development of targeted preventive strategies. To overcome these challenges, we propose several solutions and recommendations. Understanding the mechanisms underlying risk factors may inform future research aimed at developing standardized and more accurate biomarkers for PD, facilitating earlier diagnosis and improved monitoring of disease progression. Additionally, we offer actionable recommendations for PD prevention and management tailored to healthy individuals, patients diagnosed with PD, and healthcare systems. These strategies aim to improve clinical outcomes, enhance the quality of life, and optimize healthcare delivery for PD.